Facile modification on the oxygen‐inhibited layer of photopolymerized acrylates via aza‐Michael addition. Issue 6 (2nd February 2021) - Zhou, Junyi; Allonas, Xavier; Liu, Xiaoxuan; Wu, Shanghua
Abstract: In free radical UV curing, the inhibition of the photopolymerization reaction by oxygen leaves in most cases a considerable amount of acryl groups on the surface of cured materials. In the work reported, advantage was taken of the residual acryl CC double bonds as reactive sites for aza‐Michael addition in order to proceed to surface modification. A formulation composed of bisphenol A acrylate and trimethylolpropane triacrylate was cured under UV‐LED ( λ = 405 nm) and the oxygen‐inhibited surface was modified by aza‐Michael addition using several amino compounds such as tris(hydroxymethyl)methylaminomethane, amino‐polydimethylsiloxane and amino acids. The conversion of acryl CC double bonds and the content of functional groups on the surface were measured using Fourier transform infrared and X‐ray photoelectron spectroscopies and confocal Raman microscopy. After modification, the surfaces of samples exhibited diverse hydrophilicity and affinity to aqueous acid/alkali. © 2021 Society of Chemical Industry Abstract : After free radical photopolymerization of acrylates, aza‐Michael addition can be used to modify the oxygen‐inhibited surface. And amino compounds can be added to the surface, which exhibits various properties.